Utilitas Piotroski F-Score Untuk Memprediksi Return Saham Pada Periode 1 Dan Perode 2 Penerbitan Index LQ45 - Maulidi Arundina Pratama; Lindananty (LPPM UBP, 2023)
This study investigates the predictive capability of the Piotroski F-Score model in forecasting stock returns during two distinct periods following the issuance of the LQ45 index. The rationale behind dividing the testing periods lies in their temporal proximity to the announcement of audited financial statements, with period 1 being close to this announcement and period 2 occurring eight months thereafter. Such differing time intervals can potentially lead to varying investor decisions. The results of regression analysis, conducted on a sample of 30 consistently listed LQ45 stocks spanning from 2020 to 2022, reveal that the Piotroski F-Score exhibits a positive impact on stock returns during period 1, whereas its influence diminishes during period 2.